(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Chronic heart failure (CHF) is a clinical syndrome in which patients have typical complaints (shortness of breath, decreased exercise tolerance, fatigue) and objective signs (wheezing in the lungs, hepatomegaly, expansion of the jugular veins) caused by a violation of the structure and / or function of the heart (primarily the left ventricle (LV)), which leads to a decrease in cardiac output and/or an increase in intracardiac pressure at rest or during exercise. The proof of LV dysfunction is the most important argument that allows us to move from the clinical hypotheses for a confirmed diagnosis. Chronic heart failure is not an independent disease, it is a complication, the outcome of cardiac diseases that violate the anatomy and function of the heart. Therefore, an important task facing a doctor who suspects or has diagnosed a patient with CHF is to determine its cause (table). Although the treatment of CHF syndrome is universal, the impact on its cause can vary significantly. Patients with CHF of ischemic etiology need pharmacotherapy aimed at eliminating the symptoms of ischemic heart disease (CHD) (antianginal drugs) and improved prognosis (statins, antiplatelet agents, angiotensin converting enzyme (ACE) inhibitors), and /or surgical revascularization; patients with arterial hypertension (AH) require hypotensive drugs (including the possible use of calcium antagonists); if the symptoms of heart failure are due to tachyarrhythmias, treatment aimed at reducing the frequency of ventricular response, or electrical cardioversion is necessary. Congenital and acquired heart defects stand apart, because when they if the symptoms of heart failure are detected, they cannot be eliminated otherwise than by surgical operation, for example, valve replacement. Modern diagnostic methods (primarily echocardiography (EchoCG)) they allow us to distinguish two main variants of LV dysfunction in patients with CHF: in the first case, its contractile, systolic function mainly suffers, in the second – diastolic, the ability to relax. In the first case , a significant decrease in the ejection fraction is determined (LV) LV (<40%) due to local or diffuse violation of its contractility, often dilation of the cavity and thinning of the LV walls indicate CHF with reduced or low LV (CHF-nFV). In the second case, the LV remains normal, preserved (>50%), local contractility disorders are uncharacteristic, LV volume may be normal or even decrease, wall thickness is usually increased using special techniques (Doppler study of transmittal blood flow or tissue Doppler) a violation of diastolic function is detected LV (HSN with preserved PV (HSN-sFV)). Recently a subgroup of patients with CHF has been identified, in whom FV is 40-49%, but so far this has little effect on practical decision-making.